Spatial structure of Pleurothallis, Masdevallia, Lepanthes and Epidendrum epiphytic orchids in a fragment of montane cloud forest in South Ecuador - Riofrío, Lorena (Universidad de Costa Rica, 2015)
Orchids are the most diverse family of vascular plants in Ecuador with 228 genera and nearly 4000 species. More than 60% of these species are epi- phytes, being Pleurothallis R.Br., Epidendrum L., Lepanthes Sw. and Masdevallia Ruiz & Pav., with 472, 358, 314 and 226 species respectively, some of the genera with greater number of epiphytic orchids (Dodson 1994-2003).